Between uncertainty and adaptation: A sociological-organizational analysis of power relations in Universidad Nacional Mayor de San Marcos during the Covid-19 pandemic - Canelo Castillo, Gonzalo (2022)
This paper seeks to analyze the online adaptation process of the Universidad Nacional Mayor de San Marcos (UNMSM) during the COVID-19 pandemic. Two key moments were chosen for the analysis: the new modality of the admission exam and the online classes. Based on the review of institutional sources, social network publications, and news, we sought to understand the scope and limitations of the present decisions taken by the UNMSM management. The university as an organization, therefore, is understood as a space where power relations fluctuate and where it is difficult to find consensus for decisión-making. Also, the capacity of two actors with conflicting interests has been highlighted: on the one hand, the rector’s group, made up of the rector, vice-rectors, and faculty deans, and, on the other hand, students organized as a union.